Analisis Karakteristik Hujan Penyebab Aliran Debris Di Lereng Gunung Merapi - , Caecilia Ajeng N ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mount Merapi eruption that occurred on October to November 2010 gave threat of disaster to the slope area. The secondary threat came from the volcanic material deposit which will produce debris flow if mixed with storm water. The debris that flow down the slope or river bed with certain inclination will produce swift flow and become very dangerous. By considering the danger and the impact of this debris flow, and also reminding the limited data availability, it become necessary to find a simple method using rainfall data to forecast debris flow occurrence in slope of Mt. Merapi, especially in Putih River and Boyong River. Analysis to rainfall characteristic that induced debris flow was conducted using Critical line curve which published by Ministry of Land, Infrastructure and Transport Infrastructure Development Institute â Japan. This method is based on: rainfall series that induce debris flow, working rainfall (RW)